Synthesis and Evaluation the Activity of 1, 3, 4-Thiadiazole Derivatives as Antibacterial Agent Against Common Pathogenic Bacteria - Akram, Evon; Daham, Shaymaa Naji; Rashad, Alaa Adnan; Mahmood, Asmaa Easa (Al-Nahrain Journal of Science, 2019)
Schiff base compound 5-(benzylideneamino)-1,3,4-thiadiazole-2-thiol was prepared from condensation reaction of 2-amino-5-mercapto-1,3,4-thiadiazole with benzaldehyde. Schiff bases react with Copper(ӀӀ), Ferric(ӀӀӀ), Cobalt(ӀӀ) and Zinc(ӀӀ) to form four complexes. The Schiff base complexes were identification by using FTIR and UV-VIS. The antibacterial activity of complexes (Copper(ӀӀ), Ferric(ӀӀӀ), Cobalt(ӀӀ) and Zinc(ӀӀ)) were studied against S. aureus  and S . epidermidis as a model of Gram positive, E. coli, P. mirabilis, C. freundii and P. aeruginosa as a Gram negative model to determine activity of synthesized complexes, after subjected them to some tests to confirm the identity of the pathogenic bacteria. Ten antibiotics (Ampicillin and Amoxicillin) have been chosen to investigate the ability of bacterial isolates to resistant the conventional antibiotic. Imipenem have been selected to contrast its efficiency with those of the new compounds because of its high efficiency. The results exhibited higher activity of the new compounds proportional to the chosen antibiotics.